Analysis of the Use of SiBakul Jogja to Increase the Competitive Value of MSMEs Businesses in Jogja Province - Solihah, Ulfa Maratus; Bambang Septiawan (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study examines